Global Evidence on the Income Elasticity of Willingness to Pay, Relative Price Changes and Public Natural Capital Values - Moritz A. Drupp; Zachary M. Turk; Ben Groom; Jonas Heckenhahn (CESifo GmbH, 2024)
While the global economy continues to grow, ecosystem services tend to stagnate or decline. Economic theory has shown how such shifts in relative scarcities can be reflected in project appraisal and accounting, but empirical evidence has been sparse to put theory into practice. To estimate relative price changes in ecosystem services to be used for making such adjustments, we perform a global meta-analysis of contingent valuation studies to derive income elasticities of marginal willingness to pay (WTP) for ecosystem services to proxy the degree of limited substitutability. Based on 735 income-WTP pairs from 396 studies, we find an income elasticity of WTP of around 0.6. Combined with good-specific growth rates, we estimate relative price change of ecosystem services of around 1.7 percent per year. In an application to natural capital valuation of forest ecosystem services by the World Bank, we show that natural capital should be uplifted by around 40 percent. Our assessment of aggregate public natural capital yields a larger value adjustment of between 58 and 97 percent, depending on the discount rate. We discuss implications for policy appraisal and for estimates of natural capital in comprehensive wealth accounts.
Keywords: D61; H43; Q51; Q54; Q58; 330; willingness to pay; ecosystem services; income elasticity; limited substitutability; growth; relative prices; contingent valuation; forests; natural capital